Penggunaan Media Sosial Instagram Secara Berlebihan Dikalangan Anak Remaja - Muhammad Aldi Wiranata; Opah Opah; Moch Fajar Megantara; Shafira Rayna Resantari (IHSA Institute, 2022)
It is undeniable that social media has a great influence on a person’s life, including teenegers. From the time of its development, at school and outside, adolescenets try to find their identity by hanging out with their peers. This study aims to determine the influence of social media. Explain what the effect of social media are for adolescents in their development, then to find out what are the effect on adolescent behavior caused by social media, especially in the use of instagram. In this study, researchers used qualitative research methods because they wanted to explore facts, symphtoms and events pf the influence of social media on adolescent behavior in the flied as it is in the form of more complex data details about phenomena that are difficult to express by quantitative methods. The result of the quantitative research needed by researchers are in the form of in-depth in information about the influence of social media on adolescents themselves.